The psychology of the corrupt: some preliminary findings. Issue 2 (1st April 2019) - Nee, Claire; Button, Mark; Shepherd, David; Blackbourn, Dean; Leal, Sharon
Abstract : Purpose: This paper aims to present findings based on the psychological profile of 17 offenders who have been convicted of occupational fraud, bribery or related offences. It provides findings on their specific psychological profiles using well-established psychological techniques to gauge personality. The study is also aimed to provide the foundations for further research on such profiles, which could eventually provide a screening tool to identify individuals who might be a higher risk of engaging in corrupt behaviours for organisations. Design/methodology/approach: The research is based upon 17 interviews with white-collar offenders who were also asked to complete an Eysenck Personality Questionnaire to identify their profile. Findings: This study postulates that sensation seeking, risk appetite, impulsivity and lower non-aggressive self-regulation dominate the E scale traits of white-collar offenders. Originality/value: This paper is very much original in its design with few studies having been performed in this area.